Interocular symmetry and asymmetry in ocular health and disease - Cui, Hongli; Zhang, Zhengwei (Frontiers in Medicine, 2025)
In various ocular tissues, the presence of symmetry and asymmetry not only influences physiological functions but also demonstrates significant correlations with the pathogenesis and progression of multiple ophthalmic disorders. Under healthy conditions, ocular structures typically maintain a high degree of bilateral symmetry, ensuring stability and efficacy in visual perception. However, subtle interocular asymmetries may emerge due to factors including aging and environmental exposures, providing critical biological insights into visual functionality and ocular health maintenance. Under pathological circumstances, specific structural asymmetries often serve as early indicators of disease progression. Quantitative analysis of multilayer structural alterations using advanced ophthalmic imaging modalities offers valuable reference data for early disease detection and therapeutic interventions. A comprehensive investigation of ocular symmetry and asymmetry facilitates precise characterization of normative ocular architecture, thereby establishing a theoretical foundation for elucidating disease mechanisms and developing early diagnostic strategies. This multidimensional approach enhances our understanding of ocular pathophysiology and informs evidence-based clinical decision-making.